Efficacy of three-tone disclosing agent as an adjunct in caries risk assessment - Mungara Jayanthi; Mangalampally Shilpapriya; Venumbaka Nilaya Reddy; Arun Elangovan; Rajendran Sakthivel; Poornima Vijayakumar (Wolters Kluwer Medknow Publications, 2015)
Background: Today, most approaches to caries viewed that catastrophic change in normal plaque biofilm is responsible for the disease. The behavior and composition of the biofilm are a reflection of the oral environment; the caries is a reflection of adverse changes occurring in that environment. Thus, it is important to identify the pathogenicity of the plaque biofilm so as to predict the caries risk. The recently developed three-tone plaque disclosing agent was used to test its ability in identifying the pathogenicity of plaque. Aim: To assess the efficacy of three-tone plaque disclosing agent in identifying the plaque pathogenicity and correlate with the clinical caries status and microbiological findings. Materials and Methods: Sixty children of 6-13 years age group of both sexes were clinically examined for caries and plaque scores, and then disclosing agent was applied; the color stained plaque samples were collected and cultured for microbiological assessment, and the data were analyzed based on the caries status of the children. Results: There was a significant difference between the pathological plaque of caries active and caries free group (P < 0.05). The pathological plaque scores and the total colony counts, Streptococcus counts and mutans streptococci counts increased with the increase in caries. Conclusion: Three-tone plaque disclosing agent was effective in identifying pathological plaque and can be used as one of the chairside adjuvants in caries risk assessment.